Empowering women through homestead agricultural mechanization: Stories of transformation from Bangladesh - Sadaf, Bushra Humaira; Haque, Abdul; Miajy, Abdullah; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
In northern Bangladesh, where agriculture has long been a way of life, women are now emerging as entrepreneurs, transforming not just their livelihoods but the dynamics of their communities. With support from the CGIAR Research Initiative on Mixed Farming Systems, small agricultural machinery like fodder choppers, mini rice husking mills, and oil extractors are changing these women's lives.